The darfur conflict: Failure and violation of international law - Nauvally, Zharfan Surya (Trigin Publisher, 2025)
The purpose of this research is to investigate what violations have been committed by the Sudanese government and have violated international law, especially the issue of genocide and women's rights. The Darfur conflict has various problems ranging from inter-ethnic conflict and finally to genocide. There are two groups that are feuding between the Janjaweed, namely the government camp and the Sudan Liberation Movement/Army or the Sudanese Liberation Movement, abbreviated as SLM/A, and the Justice and Equality Movement, the equality and justice movement, abbreviated as JEM. And another problem is that at the start of the protracted conflict was genocide and the question arose whether international law was not considered in the country of Sudan. And by using a theoretical method or normative law research method so as to see this conflict from a statutory perspective that is rooted in international law. This study found various events, namely the mastermind behind this incident was President Omar Al-Bashir and conflict resolution must use a third party so that it can be resolved, such as the United Nations, ICC, African Union and UNIFEM.